2020
DOI: 10.1530/rep-19-0616
|View full text |Cite
|
Sign up to set email alerts
|

ERα-dependent stimulation of LCN2 in uterine epithelium during mouse early pregnancy

Abstract: Maintenance of a suitable uterine milieu is important for embryo development and subsequent implantation during early pregnancy. High estrogen level in proestrous and estrous stages is essential for uterine anti-bacterial activity during preimplantation period. Lipocalin-2 is an essential molecule which prevents bacterial infection by sequestering iron. In this study, the highest expression of lipocalin-2 is observed in the endometrial epithelium on day 1 of normal pregnancy and pseudopregnancy, which exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Estradiol-17β (0.1, 1, and 10 μg/100 μl per mouse), ERα agonist PPT (250 ng/100 μl per mouse; Merck, H6036), and ERβ agonist DPN (100 ng/100 μl per mouse; Merck, H5915) were subcutaneously injected for 12 hours. Mice were euthanized at the indicated time for further analysis ( 87 ). Ovariectomized mice were also subcutaneously injected with progesterone (1 mg/100 μl) for 1 hour for SHH detection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol-17β (0.1, 1, and 10 μg/100 μl per mouse), ERα agonist PPT (250 ng/100 μl per mouse; Merck, H6036), and ERβ agonist DPN (100 ng/100 μl per mouse; Merck, H5915) were subcutaneously injected for 12 hours. Mice were euthanized at the indicated time for further analysis ( 87 ). Ovariectomized mice were also subcutaneously injected with progesterone (1 mg/100 μl) for 1 hour for SHH detection.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was carried out as previously stated ( 87 ). After being blocked with 5% nonfat milk (A600669, Sangon, China) for 1 hour, membranes were incubated with specific primary antibodies overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed with modifications according to a previous study [ 70 ]. In brief, the uterine paraffin sections were dewaxed and dehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…For example, circulating concentrations of lcn2 are higher in women with gestational diabetes and preeclampsia, which suggests that lcn2 may be of value as a possible marker of fetal programming in humans (25). other studies conducted in humans and animal models indicated a sex specific regulation of Lcn2 by estrogen (26)(27)(28); ovariectomized mice treated with estrogen showed an increase in Lcn2 gene expression levels in white adipose tissue, liver and serum (29). This adipokine is a member of the lipocalin superfamily, characterized by the presence of three conserved motifs comprising a single eight-stranded antiparallel β-barrel similar to a calyx that is able to bind numerous ligands.…”
Section: The Gonadal Expression Pattern Of Lipocalin-2 and 24p3 Receptormentioning
confidence: 99%
“…Semi-quantitative reverse transcription PCR. Total rna from all samples was reverse transcribed using the Superscript™ First-Strand Synthesis system (invitrogen; Thermo Fisher Scientific, Inc.), according to manufacturer's protocol and as described previously (28). all reactions were carried out in a total volume of 20 µl.…”
Section: Animalsmentioning
confidence: 99%